2018
DOI: 10.18203/2320-1770.ijrcog20185404
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcome in women with eclampsia: a retrospective study at the University of Benin Teaching Hospital

Abstract: Background: Eclampsia is a serious obstetric complication with attendant high maternal and perinatal morbidity and mortality especially in the developing countries. This study aims to assess the maternal and perinatal outcomes of eclampsia and suggest ways to improve them.Methods: This was a 5-year retrospective study (2009-2013) of cases of eclampsia managed at the University of Benin Teaching Hospital, Benin City, Nigeria. The number of cases managed was obtained from records at the emergency room, labour wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…In this study, majority of the women were delivered through cesarean section. This is similar to the study by Okoror where the most common route of delivery was the abdominal route in eclamptic women [22]. However, in most studies across the world, caesarean section delivery has been repeatedly reported to be higher in women with eclampsia [23,24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, majority of the women were delivered through cesarean section. This is similar to the study by Okoror where the most common route of delivery was the abdominal route in eclamptic women [22]. However, in most studies across the world, caesarean section delivery has been repeatedly reported to be higher in women with eclampsia [23,24].…”
Section: Discussionsupporting
confidence: 88%
“…However, in most studies across the world, caesarean section delivery has been repeatedly reported to be higher in women with eclampsia [23,24]. The definitive treatment for pre-eclampsia/eclampsia is delivery through the safest and fastest route, which can either be via abdominal or vaginal delivery, thus following maternal stabilization, timely delivery improves outcomes [22,23]. It is therefore important to aid the provision of more comprehensive emergency obstetrics care centers with Volume 7; Issue 1 Gynecol Obstet, an open access journal ISSN: 2577-2236 adequate skilled manpower where eclampsia could be adequately managed so as to prevent mortality and morbidity associated with the condition.…”
Section: Discussionmentioning
confidence: 99%